2014
DOI: 10.1097/igc.0000000000000042
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Stationary Colposcope and the Gynocular, by the Swede Score Systematic Colposcopic System in VIA Positive Women: A Crossover Randomized Trial

Abstract: ObjectiveThis study aimed to evaluate cervical lesions by the Swede coloscopy system, histologic finding, liquid-based cytology, and human papillomavirus (HPV) in women who resulted positive for visual inspection of the cervix with acetic acid (VIA) by using a pocket-sized battery-driven colposcope, the Gynocular (Gynius AB, Sweden).MethodsThis study was a crossover, randomized clinical trial at the colposcopy clinic of Bangabandhu Sheikh Mujib Medical University in Dhaka, Bangladesh, with 540 VIA-positive wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 21 publications
3
45
0
Order By: Relevance
“…According to the study of Nessa et al, the Swede score colposcopic scoring system identified significantly more CIN II and higher lesions than smear results and provided more accurate screening and selection for immediate treatment of the cervical lesions in low-resource settings 19. In addition, Nessa et al suggested that the Swede score cut-off point should be 4 for biopsy in low-resource settings as an alternative cervical screening method 19. Similarly, also in our study, low-grade lesions and high-grade lesions were detected by the Swede score colposcopic scoring system with high accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…According to the study of Nessa et al, the Swede score colposcopic scoring system identified significantly more CIN II and higher lesions than smear results and provided more accurate screening and selection for immediate treatment of the cervical lesions in low-resource settings 19. In addition, Nessa et al suggested that the Swede score cut-off point should be 4 for biopsy in low-resource settings as an alternative cervical screening method 19. Similarly, also in our study, low-grade lesions and high-grade lesions were detected by the Swede score colposcopic scoring system with high accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is an overlap between Reid score 3–4 (CIN1–CIN2) and score 5–8 (CIN2–CIN3). Also there is a different management of CIN1 and CIN2 lesions . Similarly to Kushvah et al .…”
Section: Discussionmentioning
confidence: 99%
“…Nessa et al (14) evaluated cervical lesions in women with abnormal VIA findings using Swede score by Gynocular and colposcope. The cut-off value of 5 and greater for Swede score by the colposcope had a sensitivity of 83.3% (95% CI, 65.3%-94.7%) and specificity of 24.2% (95% CI, 17.9%-31.5%) Nessa et al (15) evaluated the accuracy in detecting cervical lesions by nurses versus doctors using a stationary colposcope and gynocular.…”
Section: Discussionmentioning
confidence: 99%